2018
DOI: 10.17240/aibuefd.2018..-400746
|View full text |Cite
|
Sign up to set email alerts
|

Matemati̇k Tari̇hi̇ni̇n Ortaokul Matemati̇k Ders Ki̇taplarindaki̇ Yeri̇

Abstract: ÖZETMatematik tarihinin dikkatli ve akılcı kullanımı etkili bir öğretim aracı olabilir. Bunun yollarından biri ise matematik derslerine matematik tarihini entegre etmekten geçmektedir. Entegre etme yolları içerisinde ders kitaplarının rolü ise yadsınamaz bir gerçektir. Nitekim ders kitapları öğretmen ile öğrenci arasında bir köprü özelliği taşımaktadır. Buradan hareketle bu çalışmada ortaokul matematik dersi kitaplarındaki matematik tarihi ögeleri araştırılarak matematik tarihi ile ilgili durumları dersin hang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 22 publications
0
7
0
8
Order By: Relevance
“…When the place of presentation of the elements of the history of mathematics is examined, it is seen that 52% of them are given at the beginning of the subject. Erdogan et al (2015Erdogan et al ( ), İncikabı et al (2018 and Mersin and Durmuş (2018), it is seen that most of the elements of history of mathematics are given at the beginning of the subject. It can be thought that the reason why mathematics history items are given at the beginning of the subject is to attract students' attention to the subject and to give preliminary information about the subject.…”
Section: Resultsmentioning
confidence: 99%
“…When the place of presentation of the elements of the history of mathematics is examined, it is seen that 52% of them are given at the beginning of the subject. Erdogan et al (2015Erdogan et al ( ), İncikabı et al (2018 and Mersin and Durmuş (2018), it is seen that most of the elements of history of mathematics are given at the beginning of the subject. It can be thought that the reason why mathematics history items are given at the beginning of the subject is to attract students' attention to the subject and to give preliminary information about the subject.…”
Section: Resultsmentioning
confidence: 99%
“…These categories were discussed in four parts to determine how the history of mathematics is used in the mathematics coursebooks and shown in Table 2. Next, the coursebooks were subjected to content analysis again according to the content classification of Mersin and Durmuş (2018) and Tzanakis and Arcavi (2000). In addition, the coding of the historical elements used in the coursebooks, the content, the usage methods, the stage of the course, the learning domain, and how this situation changed according to the grade levels with regards to the history of mathematics were carried out by three different experts.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, İncıkabı et al (2019) examined 8 mathematics coursebooks used in 2016-2017 and reached 15 EHMs. Additionally, Mersin and Durmuş (2018) stated that they found out 19 items from 4 coursebooks in their study in which they examined the coursebooks used in the same years. Tan Şişman and Kirez (2018) suggested that 27 historical elements were included in 6 mathematics coursebooks used in 2015-2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of EHM contents of items according toMersin and Durmuş (2018) …”
mentioning
confidence: 99%